2011
DOI: 10.1177/0143034311415908
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive behavioural group approach for adolescents with disruptive behaviour in schools

Abstract: Cognitive behavioural approaches emphasize the links between thoughts, feelings and behaviour (Greig, 2007). Previous research has indicated that these approaches are efficacious in reducing disruptive behaviour in adolescents. The aim of the current study was to provide further evaluation of cognitive behavioural group work to reduce disruptive behaviour with this population and to determine if improvements made were maintained in the longer term. The sample comprised 22 adolescents aged 13-to 14-years-old id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…Rather, the primary implications for organizational policy are an emphasis on intervening in employees' problematic stress-management strategies. Moreover, given strong evidence from longitudinal analyses, which has indicated that personality traits are malleable throughout the life course (Roberts & Mroczek, 2008), our findings also suggest that organizational policy may benefit from the inclusion of trait EI training practices, which have been shown to have long-term effects in trait EI and consequently in mental health (Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009;Ruttledge & Petrides, 2012).…”
Section: Discussionmentioning
confidence: 60%
“…Rather, the primary implications for organizational policy are an emphasis on intervening in employees' problematic stress-management strategies. Moreover, given strong evidence from longitudinal analyses, which has indicated that personality traits are malleable throughout the life course (Roberts & Mroczek, 2008), our findings also suggest that organizational policy may benefit from the inclusion of trait EI training practices, which have been shown to have long-term effects in trait EI and consequently in mental health (Nelis, Quoidbach, Mikolajczak, & Hansenne, 2009;Ruttledge & Petrides, 2012).…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, since trait EI is a predictor of various outcomes (e.g., physical and psychological health) and is not a rigid personality trait immune to change (Nelis et al, 2009), interventions targeting the modification of parenting styles could play an important role in the prevention of behavioral or psychological problems through the optimization of trait EI. Our study provides some evidence that Ruttledge and Petrides' (2012) suggestion to include parents in interventions attempting to improve adolescent behavioral problems through the optimization of trait EI, would have a positive effect and might make the results of the intervention program more stable in time and across various contexts. Parenting style, along with other variables, such as temperament and cultural values, may constitute a key factor of the mechanism through which trait EI is being shaped, and a key target for the prevention of problems arising in socio-emotional development.…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, a positive/consistent emotional climate allowing free expression of emotions is expected to lead in emotional competence (Morris et al, 2007) and, thus, strong emotional self-perceptions. Findings suggesting that trait EI can be improved after training (Nelis, Quoidbach, Mikolajczak & Hansenne, 2009;Ruttledge & Petrides, 2012), providing evidence for the flexibility of this characteristic, make the investigation of this relationship even more critical from a practical perspective. Specifically, our study aims to develop better understanding of how parenting styles contribute to the development of trait EI, with the long term goal of advancing our knowledge of how parenting styles could serve as a prime intervention target to improve trait EI and, consequently, prevent adolescent behavioral problems or other conditions that could emerge due to poorly developed trait EI (Gugliandolo et al, 2015).…”
Section: Present Studymentioning
confidence: 99%
“…There is additional evidence from similarly rigorous research that trait EI training has long‐term (lasting for at least 1 year) beneficial effects in terms of reducing perceived stress levels, somatic complaints, and even diurnal cortisol secretion, a biological marker for stress (Kotsou, Nelis, Gregoire, & Mikolajczak, ). Preliminary research with young adolescents has suggested that cognitive behavioral group‐work (Ruttledge & Petrides, ) or yoga interventions (McIlvain, Miller, Lawhead, Barbosa‐Leiker, & Anderson, ) can have positive effects on trait EI scores (see also Khalsa, Greiner‐Ferris, Hofmann, & Khalsa, ). Collectively, this evidence is important both for its practical consequences in people's lives and for what it implies about the causal effects of trait EI on a range of psychological and behavioral outcomes.…”
Section: Discussionmentioning
confidence: 99%